Primary Peritonitis Secondary to Streptococcus pyogenes in a Young Female Adult-A Case Report and Literature Review - Avelyn E. Y. Aw; James W. K. Lee; Kon Voi Tay (MDPI AG, 2021)
Primary spontaneous bacterial peritonitis (SBP) is a rare cause of acute abdomen in previously healthy patients, even more unusually caused by a group A Streptococcus (GAS) (also known as Streptococcus pyogenes) infection. We report a young, otherwise healthy female who presented with generalized abdominal pain that was initially managed conservatively as gastroenteritis, with a computed tomography (CT) scan showing a ruptured corpus luteal cyst. Upon subsequent readmission with worsened pain and symptoms, a repeat CT scan showed worsened free fluid with signs of peritonitis. A diagnostic laparoscopy confirmed primary peritonitis with an unknown infection source and causative pathology, as the appendix, ovaries and bowels were healthy-looking. Fluid cultures returned positive for GAS Pyogenes, while blood and urine cultures were negative. The discussion reviews the challenges in diagnosis and treatment of GAS primary peritonitis, highlighting the need for clinical suspicion, early diagnosis via laparoscopy or laparotomy and prompt antibiotic therapy as the current standard for treatment.